2021
DOI: 10.1002/lno.11997
|View full text |Cite
|
Sign up to set email alerts
|

Pelagic N2 fixation dominated by sediment diazotrophic communities in a shallow temperate estuary

Abstract: Estuaries receive substantial anthropogenic nitrogen loading and are mainly considered net nitrogen sinks. While several studies have identified diverse diazotrophic communities in estuarine sediments, the role of pelagic diazotrophs in these systems is not well understood. We investigated the links between diazotrophic community composition, nitrogenase (nifH) gene expression, N 2 fixation, and environmental conditions in Narragansett Bay (USA). Pelagic N 2 fixation rates ranged between 0.02 and 9.41 nmol N L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Aquatic studies have traditionally focused on photoautotrophic cyanobacterial diazotrophs inhabiting oligotrophic and sunlit environments where energy is made available via photosynthetic carbon fixation ( Zehr, 2011 ). However, during the last decade it has become evident that non-cyanobacterial diazotrophs (NCDs; see Box 1 ) have an almost ubiquitous distribution in pelagic environments ( Farnelid et al, 2011 ; Langlois et al, 2015 ; Geisler et al, 2020 ; Hallstrøm et al, 2021 ; Messer et al, 2021 ). For instance, the presence and/or expression of the nitrogenase gene ( nifH ) by NCDs has been reported from low latitude open oceans ( Halm et al, 2011 ; Moisander et al, 2014 ; Langlois et al, 2015 ) to environments previously not regarded as suitable for N 2 fixation such as eutrophic rivers, estuaries and coastal waters ( Mulholland et al, 2012 ; Bentzon-Tilia et al, 2015 ; Geisler et al, 2020 ; Hallstrøm et al, 2021 ), the aphotic deep sea ( Rahav et al, 2013 ; Benavides et al, 2015 ), and nutrient-rich arctic waters ( Harding et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic studies have traditionally focused on photoautotrophic cyanobacterial diazotrophs inhabiting oligotrophic and sunlit environments where energy is made available via photosynthetic carbon fixation ( Zehr, 2011 ). However, during the last decade it has become evident that non-cyanobacterial diazotrophs (NCDs; see Box 1 ) have an almost ubiquitous distribution in pelagic environments ( Farnelid et al, 2011 ; Langlois et al, 2015 ; Geisler et al, 2020 ; Hallstrøm et al, 2021 ; Messer et al, 2021 ). For instance, the presence and/or expression of the nitrogenase gene ( nifH ) by NCDs has been reported from low latitude open oceans ( Halm et al, 2011 ; Moisander et al, 2014 ; Langlois et al, 2015 ) to environments previously not regarded as suitable for N 2 fixation such as eutrophic rivers, estuaries and coastal waters ( Mulholland et al, 2012 ; Bentzon-Tilia et al, 2015 ; Geisler et al, 2020 ; Hallstrøm et al, 2021 ), the aphotic deep sea ( Rahav et al, 2013 ; Benavides et al, 2015 ), and nutrient-rich arctic waters ( Harding et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…An exception occurred in the suspended particle fraction at station 2, where UCYN-A accounted only for 3% of the reads and Crocosphaera dominated instead (94.5% cyanobacterial, 58% overall reads), becoming the second most abundant cyanobacterial group. While Crocosphaera is typically low or unreported in the northeast compared to the southwest Atlantic [33,34], high abundances have been linked to high N 2 xation rates measured in anticyclonic eddies in the North Paci c [19,31]. In this study, 99% of the Crocosphaera sequences were found between stations 1 and 3, seemingly forming a bloom at the eastern edge of the eddy.…”
Section: Cyanobacteriamentioning
confidence: 54%
“…Switching the trimming approach from one based on individual read quality profiles (using truncQ in Table 3) to fixed-length trimming based on overall quality profiles of the forward and reverse reads (using truncLen.fwd and truncLen.rev in Table 2) resulted in more reads being retained for some studies (Sato et al, 2021; Selden et al, 2021; Hallstrøm et al, 2022b; Gradoville et al, 2020). However, fixed-length trimming would have required the selection of trim lengths based on visual, qualitative assessments of hundreds of FASTQ quality plots which is difficult to accomplish in a systematic manner.…”
Section: Resultsmentioning
confidence: 99%